2021
DOI: 10.1155/2021/8628335
|View full text |Cite
|
Sign up to set email alerts
|

Computational Learning Model for Prediction of Heart Disease Using Machine Learning Based on a New Regularizer

Abstract: Heart diseases are characterized as heterogeneous diseases comprising multiple subtypes. Early diagnosis and prognosis of heart disease are essential to facilitate the clinical management of patients. In this research, a new computational model for predicting early heart disease is proposed. The predictive model is embedded in a new regularization based on decaying the weights according to the weight matrices’ standard deviation and comparing the results against its parents (RSD-ANN). The performance of RSD-AN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…This approach prevents the learning model from using a wide range of weight space by multiplying the standard deviation of the weight matrix by its parameter to obtain its regularization term. The standard deviation measures the spread of the weight values within the matrix and is computed by taking the square root of the variance of the weights [ [31] , [32] , [33] , [34] , [35] ]. …”
Section: Methodsmentioning
confidence: 99%
“…This approach prevents the learning model from using a wide range of weight space by multiplying the standard deviation of the weight matrix by its parameter to obtain its regularization term. The standard deviation measures the spread of the weight values within the matrix and is computed by taking the square root of the variance of the weights [ [31] , [32] , [33] , [34] , [35] ]. …”
Section: Methodsmentioning
confidence: 99%
“…Among the applied classifiers, they found that the Random Forest classifier yields the highest accuracy of 96.28%. A computational model for detecting heart abnormality is developed by the authors of [19]. This model incorporates a suggested regularizer with artificial neural network.…”
Section: Related Workmentioning
confidence: 99%
“…On the basis of retaining the original multi-dimensional features, we tried to use the embedded method to filter features for the establishment of the sleep staging model. The embedded method is a feature filtering method that uses machine learning algorithms and models to obtain the weight coefficients of each feature and then selects features based on the coefficients from largest to smallest [ 28 ]. If the feature set filtered by the embedded method can achieve the same staging accuracy, the cost of computing sleep staging will be reduced in practical applications.…”
Section: Inductionmentioning
confidence: 99%